A FANA' AND BAQA' ACCORDING TO ALUSI'S PERSPECTIVE (AN EXAMINATION OF AL-ALUSI'S INTERPRETATION IN TAFSIR RUH AL-MA'ANI) - muhammad zaki, zaki; Zulyadain (UIN Mataram, 2023)
Abstract: In Sufism discourse, the concepts of fana' and baqa' become an important foundation for Islamic commentators to base their views of interpretation when encountering verses related to fana' and baqa'. So this paper tries to provide an explanation of the interpretation of isyari carried out by al-Alusi on verses related to the concepts of mortal 'and baqa' from interpretation that lead to the interpretation of isyari. al-Alusi interpretation seems to reflect the tendency to uncover the inner meaning of the Qur'an, not only revealing the outer meaning of the verse but inviting to use intuition to uncover the meaning behind the verse. Keywords: al-Alusi, Fana', Baqa'.